Gastric fluid used to assess changes during the latency period in preterm prelabor rupture of membranes. (August 2018) - Musilova, Ivana; Andrys, Ctirad; Hornychova, Helena; Pliskova, Lenka; Drahosova, Marcela; Zednikova, Barbora; Bolehovska, Radka; Faist, Tomas; Jacobsson, Bo; Kacerovsky, Marian
Abstract Objective To determine changes in the intraamniotic environment during the latency period using paired amniotic and gastric fluid samples in pregnancies complicated by preterm prelabor rupture of membranes (PPROM). Methods A total of 34 women with singleton pregnancies complicated by PPROM prior to 34 weeks were included in the study. Amniotic fluid was obtained by transabdominal amniocentesis at the time of admission. Immediately after delivery, umbilical cord blood and gastric fluid were obtained. Result Microorganisms in amniotic and gastric fluid samples were found in 38% and 59% of women, respectively. Bedside IL-6 levels were higher in amniotic than in gastric fluid in pregnancies without fetal inflammatory response syndrome (FIRS) (263 pg/mL vs. 50 pg/mL;p  < 0.0001), but not in pregnancies with FIRS (318 pg/mL vs. 444 pg/mL;p  = 0.91). Funisitis and FIRS was associated with the highest bedside IL-6 levels in gastric fluid. A gastric fluid bedside IL-6 level of 275 pg/mL was found to be the ideal cutoff value to predict funisitis and FIRS. Conclusions The microbial and inflammatory status of the intraamniotic compartment changes during the latency period in PPROM. Bedside IL-6 assessment of gastric fluid may be useful in the rapid diagnosis of funisitis and FIRS.